Selected Genetic Polymorphisms Associated with Hypoxia and Multidrug Resistance in Monoclonal Gammopathies Patients - Almasi, Martina; Besse, Lenka; Brozova, Lucie; Jarkovsky, Jiří; Bezdekova, Renata; Pour, Luděk; Minarik, Jiří; Kessler, Petr; Pavlíček, Petr; Roziakova, Lubica; Penka, Miroslav; Hájek, Roman; et al. (Klinicka onkologie, 2018)
BACKGROUND: Adaptive response to hypoxia is regulated by several mechanisms and transcription factors, including hypoxia-inducible factors (HIFs). Activation of HIF-1α is associated with increased expression of P-glycoprotein and multidrug resistance in cancer cells. In this retrospective study, we analyzed candidate single-nucleotide polymorphisms (SNPs) in HIF-1α and HIF-1β associated with risk of monoclonal gammopathy of undetermined significance (MGUS) or multiple myeloma (MM). PATIENTS AND METHODS: Genotypes of SNPs associated with hypoxia were determined in an independent cohort of monoclonal gammopathies (MG) (275 MM and 228 MGUS patients) and in 219 cancer-free controls by real time polymerase chain reaction allelic discrimination. RESULTS: When MM patients were compared to controls, protective role of CG genotype compared to CC in HIF-1β (rs2228099) for MM development was observed (OR = 0.65; CI 0.45-0.95; p = 0.026). Even after adjustment for patients' age and body mass index (BMI), there were significantly lower odds (OR = 0.55; p = 0.045) of developing MM patients of CG genotype in comparison to CC genotype. Log-rank test confirmed association of GT haplotype (rs11549467, rs2057482) in HIF-1α with better overall survival (median 41.8 months; (CI 35.1-48.5)) for "none GT" and median 93.8 months (CI 31.3-156.4) for "at least one GT" haplotype (p = 0.0500). Further, significant associations between SNPs in MDR1 and outcome of MM were found in 110 MM patients that underwent bortezomib-based treatment. CONCLUSION: Our study showed a genetic predisposition for risk of MG development and/or outcome of MM patients; nevertheless, further studies are needed to confirm our initial analysis.
Keywords: Male; Genetic Predisposition to Disease; Middle Aged; doba přežití bez progrese choroby; Paraproteinemias; proteiny spojené s mnohočetnou rezistencí k lékům; multiple myeloma - hypoxia - genotype - polymorphism - qPCR.; Hypoxia; Aged; faktor 1 indukovatelný hypoxií - podjednotka alfa; senioři; mužské pohlaví; jednonukleotidový polymorfismus; P-glykoproteiny; mnohočetná léková rezistence; Multidrug Resistance-Associated Proteins; Aryl Hydrocarbon Receptor Nuclear Translocator; Polymorphism, Single Nucleotide; lidé; receptory aromatických uhlovodíků - jaderný translokátor; ženské pohlaví; Humans; Drug Resistance, Multiple; ATP Binding Cassette Transporter, Subfamily B; Hypoxia-Inducible Factor 1, alpha Subunit; Female; Progression-Free Survival; lidé středního věku; hypoxie; genetická predispozice k nemoci; paraproteinemie